The role of tenascin c in differential diagnosis of acute decompensated systolic heart failure and acute exacerbation phase of chronic obstructive pulmonary disease - Celik, A.; Altas, Y.; Kobat, M. A.; Balin, M. (Wiley-Blackwell, 2014)
[Abstract Not Available]